(untitled) (Nóema, 2012)
In a phenomenological agenda there is no room for the man-animal question. However, in the last period of his researches, Husserl addressed repeatedly the issue, in the context of a transcendental-phenomenological analysis of the constitution of the human world. Husserl’s phenomenology proofs itself to be a non-ideological way to enquire about man and animal, rethinking their differences and their continuity, by moving from the experience of life and world.